Multiple Liver Abscess - Andi Zainal; Dona Alfina; Heru Kurniawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2003)
Liver abscess is a public health problem in few countries in Asia, Africa, and South America.1 As time goes, there were only few cases of amebic liver abscess found in developed countries, on the contrary more pyogenic liver abscess are found in those countries.2 Liver abscess could be caused by bacteria, parasite, or fungus 2. The common symptoms among the liver abscess are fever, chill, fatigue, loss of appetite, weight loss, right upper abdominal pain,2,4 in a few cases have symptoms like coughing, hiccup, pain in low right chest, or pain on the shoulder. We reported a male patient 38 years batak ethnic was admitted with major symptoms such as high fever follow by chill, right upper abdominal pain, nausea, vomiting, appetite loss, fatigue and sometimes coughing. Based on clinical, laboratory data, and abdominal USG found this patient suspected suffered from pyogenic liver abscess. Treatment of this patient consist of antibiotic (cefotaxime 2x1 IV, metronidazol 3x500mg orally and aspiration of the liver abscess). Aspiration was done 2 times with the interval 1 week, extracted 260cc totally yellow greenish watery fluid with no smell. On the follow up abdominal USG was repeated on Janurary 8, 2003 found enlarge of the liver, 3 small abscesses on the right lobe liver and so recovery process and then patient left the hospital in good condition after 3 weeks hospitalized. Keywords: Multiple liver abscess, public health problem, pyogenic liver abscess